The Effect of Organizational Change and the Implementation of Good Corporate Governance on Employee Performance with Creativityas an Intervening Variable in the Field of Planning, Distribution, and Commerce and Customer Management PT PLN (Persero) North Sumatra UID - Muhammad Iqbal Fauzi; Sri Rahayu (Equivalent : Journal of Economic, Accounting and Management, 2026)
The purpose of this study is to analyze how organizational change and the implementation of Good Corporate Governance (GCG) affect employee performance, with creativity as an intermediary factor in the aspects of planning, distribution, sales, and customer management at PT PLN (Persero) UID North Sumatra. A quantitative research method was used, with a survey approach. The research sample consisted of 99 employees, selected using a saturated sampling method. Data analysis was conducted using the Partial Least Square (PLS) technique. The results of the study indicate that organizational change and the implementation of Good Corporate Governance have a positive and significant impact on employee performance. In addition, these two factors are also proven to have a positive and significant influence on employee creativity. Creativity positively and significantly affects employee performance and serves as a mediating factor in the relationship between organizational change and the implementation of Good Corporate Governance on employee performance. Consequently, improved employee performance can be achieved by managing organizational change efficiently and implementing Good Corporate Governance, while simultaneously encouraging employee creativity.